2023
DOI: 10.1186/s13058-023-01617-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic intratumor heterogeneity of breast cancer patient-derived organoids may reflect the unique biological features of the tumor of origin

Abstract: Background The intratumor heterogeneity (ITH) of cancer cells plays an important role in breast cancer resistance and recurrence. To develop better therapeutic strategies, it is necessary to understand the molecular mechanisms underlying ITH and their functional significance. Patient-derived organoids (PDOs) have recently been utilized in cancer research. They can also be used to study ITH as cancer cell diversity is thought to be maintained within the organoid line. However, no reports investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This suggests a higher success rate than previously reported 15 . As previously reported, tumors with high proliferative potential, such as a higher nuclear grade and Ki‐67 index, were more likely to be successfully established 17,19 . However, we found that no noticeable dissimilarity was present among distinct grades or different Ki‐67 index cohorts.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This suggests a higher success rate than previously reported 15 . As previously reported, tumors with high proliferative potential, such as a higher nuclear grade and Ki‐67 index, were more likely to be successfully established 17,19 . However, we found that no noticeable dissimilarity was present among distinct grades or different Ki‐67 index cohorts.…”
Section: Discussionsupporting
confidence: 55%
“…15 As previously reported, tumors with high proliferative potential, such as a higher nuclear grade and Ki-67 index, were more likely to be successfully established. 17,19 However, we found that no noticeable dissimilarity was present among distinct grades or different Ki-67 index cohorts. It is possible that a greater percentage of chemotherapy treatment was frequently associated with higher Ki-67 index groups.…”
Section: Discussionmentioning
confidence: 54%
“…This suggests that PDO-specific cell clusters reflect different PDO properties. Moreover, they subjected two other BC tissues or PDO pairs to RNA-seq and revealed that although a complete one-to-one correspondence was not achieved, PDOs retained some degree of tumor heterogeneity of the original tissue after successive passages (40).…”
Section: Bc Pdos Recapitulate the Heterogeneity Of Original Tissuesmentioning
confidence: 99%
“…The smaller initial sample, which is hard to expand quickly enough to meet the cell amount required for drug sensitivity analysis, will also prolong the detection cycle. Breast cancer samples also face the same situation, clinicians prefer the less invasive puncture biopsy method for sampling (11,12) . Usually, the puncture tissue can obtain less tumor cells, which will directly lead to the extension of the organoid culture cycle in the existing organoid culture system, and it is di cult to provide timely diagnosis and treatment suggestions for patients.…”
Section: Introductionmentioning
confidence: 99%